2020
DOI: 10.3390/cells9020319
|View full text |Cite
|
Sign up to set email alerts
|

Tspan8-Tumor Extracellular Vesicle-Induced Endothelial Cell and Fibroblast Remodeling Relies on the Target Cell-Selective Response

Abstract: Tumor cell-derived extracellular vesicles (TEX) expressing tetraspanin Tspan8-alpha4/beta1 support angiogenesis. Tspan8-alpha6/beta4 facilitates lung premetastatic niche establishment. TEX-promoted target reprogramming is still being disputed, we explored rat endothelial cell (EC) and lung fibroblast (Fb) mRNA and miRNA profile changes after coculture with TEX. TEX were derived from non-metastatic BSp73AS (AS) or metastatic BSp73ASML (ASML) rat tumor lines transfected with Tspan8 (AS-Tspan8) or Tspan8-shRNA (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 125 publications
(157 reference statements)
2
17
0
Order By: Relevance
“…Exosomes are highly enriched in tetraspanins, particularly CD63 and CD151, in addition to diverse intracellular components, including diverse RNA species, metabolites, and proteases [ 10 , 121 , 123 ]. Given the nature and signaling capabilities of TEMs, it is of no surprise that many tetraspanins are regarded as key contributors to a variety of exosome-associated functional roles, ranging from tumor cell migration, angiogenesis and signal transduction to expression of critical cancer genes and tumor metabolism through control of micro-RNA or non-coding RNA or metabolite pools [ 67 , 124 , 125 ]. In case of CD151, it is suggested to act in concert with TSPAN8 to drive exosome production in both tumor and endothelial cells, thereby facilitating tumor metastasis [ 30 , 118 ].…”
Section: Molecular Basis For Functional and Signaling Versatility Of Cd151 And Other Tetraspaninsmentioning
confidence: 99%
“…Exosomes are highly enriched in tetraspanins, particularly CD63 and CD151, in addition to diverse intracellular components, including diverse RNA species, metabolites, and proteases [ 10 , 121 , 123 ]. Given the nature and signaling capabilities of TEMs, it is of no surprise that many tetraspanins are regarded as key contributors to a variety of exosome-associated functional roles, ranging from tumor cell migration, angiogenesis and signal transduction to expression of critical cancer genes and tumor metabolism through control of micro-RNA or non-coding RNA or metabolite pools [ 67 , 124 , 125 ]. In case of CD151, it is suggested to act in concert with TSPAN8 to drive exosome production in both tumor and endothelial cells, thereby facilitating tumor metastasis [ 30 , 118 ].…”
Section: Molecular Basis For Functional and Signaling Versatility Of Cd151 And Other Tetraspaninsmentioning
confidence: 99%
“…It was hypothesized that T-span8 interacts with integrins for MMP transcription or with G-coupled protein receptors (GPCRs), regulating various signaling pathways. In subsequent studies, overexpression of Tspan8 was found to selectively recruit CD49d into EVs, which is essential for their uptake and EC activation in a VEGF-independent manner, specifically promoting proliferation and migration as well as survival and differentiation of EC progenitors [ 83 , 84 ]. Almost a decade later, more simplified in vitro incubation of pancreatic tumor cell-derived EVs with human umbilical vein endothelial cells (HUVEC) led to observations of dynamin-dependent endocytosis of tumor-EVs and enhanced tube formation associated with the activation of Akt and ERK1/2 in ECs [ 85 ].…”
Section: Stromal Cells Evs-mediated Crosstalkmentioning
confidence: 99%
“…Gesierich et al (2006) firstly reported that TSPAN8 is the strongest angiogenesis inducer, as that overexpression of TSPAN8 in tumor cells markedly increases angiogenesis in vivo and in vitro, and co-culture of TSPAN8 knockdown tumor cells or the exosomes-depleted supernatant with HUVECs markedly inhibit HUVECs tube formation in vitro (Gesierich et al, 2006;Akiel et al, 2016). Mechanistically, the tumor cells released exosomes containing TSPAN8 are taken up by target cells via ligands for TSPAN8-associated molecules, and induce angiogenic gene transcription and modulate the RNA profile in ECs or adjacent fibroblasts, and exosomes expressing TSPAN8-CD49d complex preferentially bind ECs, thus initiating an angiogenic loop by inducing TSPAN8 itself expression on sprouting ECs (Gesierich et al, 2006;Nazarenko et al, 2010;Mu et al, 2020). The contribution of TSPAN8 and TSPAN24 on angiogenesis has also been confirmed by TSPAN8-KO mice, TSPAN24-KO mice and TSPAN8/24 double-KO mice (Takeda et al, 2007;Zhao et al, 2018a,b) (Supplementary Table 1).…”
Section: The Current Understanding Of Tetraspanins Family In Vascularmentioning
confidence: 99%
“…The contribution of TSPAN8 and TSPAN24 on angiogenesis has also been confirmed by TSPAN8-KO mice, TSPAN24-KO mice and TSPAN8/24 double-KO mice (Takeda et al, 2007;Zhao et al, 2018a,b) (Supplementary Table 1). Mechanistically, promotion of angiogenesis by tumor-derived exosomes and rescue of impaired angiogenesis in KO mice by wild type-serum exosomes depend on the association of TSPAN8 and TSPAN24 with GPCR and RTK in ECs and tumor cells (Zhao et al, 2018b;Mu et al, 2020). Most importantly, the TSPAN24integrin complex as a functional unit, and the YRSL motif of TSPAN24 plays key role in TSPAN24-mediated angiogenesis (Sincock et al, 1999;Zhang et al, 2002;Zuo et al, 2010;Liu et al, 2011;Peng et al, 2013;Huang et al, 2016).…”
Section: The Current Understanding Of Tetraspanins Family In Vascularmentioning
confidence: 99%
See 1 more Smart Citation